2019
DOI: 10.1590/1806-9282.65.8.1061
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatic adipocyte biomarkers and foot pain associated with flatfoot in schoolchildren with obesity

Abstract: SUMMARY OBJECTIVE The aim of this study was to determine the potential association of foot pain and plasmatic adipocytes as physiological biomarkers of childhood obesity with the incidence of flatfoot in a cohort of Egyptian school children aged 6 -12 years. METHODS A total of 550 Egyptian schoolchildren (220 boys and 330 girls) aged 6-12 years were randomly invited to participate in this descriptive survey analysis. For all children, we assessed the diagnosis and severity of flatfoot as well as plasma adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Obesity also leads to anatomical deformity; a study conducted in Egypt among schoolchildren explicitly shows that the occurrence of flat foot was high among obese children. e presence of flat foot leads to foot pain which is significantly manifested with increased level of adipocyte cytokines, as well as adiponectin, leptin, resistin, Il-6, and TNF-α, compared to subjects with normal BMI [71]. Physical inactiveness like slow waking/decreased velocities [72,73] and mental comorbidities [72] were also other consequences of obesity.…”
Section: Health Impact Of Obesitymentioning
confidence: 99%
“…Obesity also leads to anatomical deformity; a study conducted in Egypt among schoolchildren explicitly shows that the occurrence of flat foot was high among obese children. e presence of flat foot leads to foot pain which is significantly manifested with increased level of adipocyte cytokines, as well as adiponectin, leptin, resistin, Il-6, and TNF-α, compared to subjects with normal BMI [71]. Physical inactiveness like slow waking/decreased velocities [72,73] and mental comorbidities [72] were also other consequences of obesity.…”
Section: Health Impact Of Obesitymentioning
confidence: 99%
“…Comparable to our results, other authors [16,21] showed that in children with excessive body mass atter MLA is more prevalent than in their peers with normal body weight. The ndings from a study performed on 550 Egyptian school children showed that obese pupils were 6.1 times more likely to have a at foot and 8.5 times more likely to experience foot pain [22]. Overweight and children with obesity with at foot have a higher level of adipocytes cytokinesis than their peers with normal weight status [22].…”
Section: Mauch Et Almentioning
confidence: 99%
“…The ndings from a study performed on 550 Egyptian school children showed that obese pupils were 6.1 times more likely to have a at foot and 8.5 times more likely to experience foot pain [22]. Overweight and children with obesity with at foot have a higher level of adipocytes cytokinesis than their peers with normal weight status [22]. Sadeghi-Demneh et al [4] in a group of 667 children aged from 7 to 14 years showed that children with obesity more often than their peers with the normal body weight felt foot pain during participation in physical activity.…”
Section: Mauch Et Almentioning
confidence: 99%
“…Of these, more than 650 million (13%) were categorised as obese [1]. Obesity is a noted public health concern and is linked to several internal medicine diseases, including diabetes, cardiovascular diseases and cancers [2,3] and also affects the musculoskeletal system, particularly the foot and ankle [4,5]. For example, a number of studies T A B L E 1.…”
Section: Introductionmentioning
confidence: 99%